DESIGN OF ACCOUNTING SYSTEM AND FINANCIAL REPORTING IN PT. AUTO 88 INDONESIA - Alice Alice; Natalis Christian (Universitas Internasional Batam, 2022)
Practical Work is done with the purpose to simplify transaction recording and produce financial reports for PT. Auto 88 Indonesia according to accounting principles that apply to MSMEs. Transaction recording of PT. Auto 88 Indonesia is done manually with Microsoft Excel, and financial report is not made. The solution to this problem is the creation of a computer-based program using Microsoft Access to record transactions and produce MSME financial reports. Data collection for the program is carried out by conducting interviews and operational observations of MSMEs. The accounting program with Microsoft Access is designed to match the data collected from the interviews. The financial reports produced in this program start from the profit/loss report, changes in equity report, statement of financial position, and so on. Implementation of Access program at PT. Auto 88 Indonesia by the owner is carried out after the program produced is in accordance with the needs. PT. Auto 88 Indonesia can record transactions in accordance with applicable MSME accounting principles and can produce financial reports. Thus, PT. Auto 88 Indonesia can find out new information that could not be known before through manual recording. Accounting records can be done neatly and systematically compared to before.